Autolyzed Saccharomyces cerevisiae as a single cell protein for broiler diet (Bangladesh Journal of Animal Science, 2019)
Microbial protein often called as single cell proteins (SCP) are becoming a potential alternative to conventional protein rich ingredients in poultry diet. An experiment was conducted to know the possibility of using Saccharomyces cerevisiae derived SCP in broiler diet. A total of 96 male Ross-308 day old chicks were assigned to four diet comprising control (0% replacement), 25% replacement, 50% replacement and 100% replacement of protein concentrate with autolyzed S. cerevisiae. Each group had 6 replicates of 4 chicks in each. Body weight, body weight gain, daily weight gain, feed intake and feed conversion ratio were not affected (P>0.05) in case of 25% and 50% replacements. However, 100% replacement had resulted numerically negative effect as compared to control group. Dressing percentage and other carcass characteristics were not affected (P>0.05) in the replacement groups. The results of this study indicated that autolyzed S. cerevisiae might be used to replace protein concentrate at 25% to 50% level in broiler diet without affecting growth and carcass quality.Bang. J. Anim. Sci. 2019. 48 (1): 1-8